Numerical investigation and prediction of phase separation in diverging T-junction - Ejaz, F. (Emerald Group Holdings Ltd., 2022)
Purpose: In plethora of petroleum, chemical and heat transfer applications, T-junction is often used to partially separate gas from other fluids, to reduce work burden on other separating equipment. The abundance of liquid carryovers from the T-junction side arm is the cause of production downtime in terms of frequent tripping of downstream equipment train. Literature review revealed that regular and reduced T-junctions either have high peak liquid carryovers (PLCs) or the liquid appears early in the side arm liquid carryover threshold (LCT). The purpose of this study is to harvest the useful features of regular and reduced T-junction and analyze diverging T-junction having upstream and downstream pipes. Design/methodology/approach: Volume of fluid as a multiphase model, available in ANSYS Fluent, was used to simulate airâwater slug flow in five diverging T-junctions for eight distinct velocity ratios. PLCs and LCT were chosen as key performance indices. Findings: The results indicated that T (0.5â1) and (0.8â1) performed better as low liquid carryovers and high LCT were achieved having separation efficiencies of 96% and 94.5%, respectively. These two diverging T-junctions had significantly lower PLCs and high LCT when compared to other three T-junctions. Results showed that the sudden reduction in the side arm diameter results in high liquid carryovers and lower LCT. Low water and air superficial velocities tend to have low PLC and high LCT. Research limitations/implications: This study involved working fluids air and water but applies to other types of fluids as well. Practical implications: The novel T-junction design introduced in this study has significantly higher LCT and lower PLC. This is an indication of higher phase separation performance as compared to other types of T-junctions. Because of lower liquid take-offs, there will be less frequent downstream equipment tripping resulting in lower maintenance costs. Empirical correlations presented in this study can predict fraction of gas and liquid in the side arm without having to repeat the experiment. Social implications: Maintenance costs and production downtime can be significantly reduced with the implication of diverging T-junction design. Originality/value: The presented study revealed that the diameter ratio has a significant impact on PLC and LCT. It can be concluded that novel T-junction designs, T2 and T3, achieved high phase separation; therefore, it is favorable to use in the industry. Furthermore, a few limitations in terms of diameter ratio are also discussed in detail. Â© 2022, Emerald Publishing Limited.